Central nervous system tuberculosis and adjuvant corticosteroid therapy - Rahman, Sardar Md Lutfur; Basher, A; Rashid, M; Islam, M; Kuddus, R; Arif, SM; Faiz, MA (Mymensingh Medical Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Mymensingh Med J. 2009 Jan;18(1):47-51. The abstract of this article is available on the PubMed website